Next generation prophylactic human papillomavirus vaccines. Issue 5 (May 2015) - Schiller, John T; Müller, Martin
Summary: The two licensed bivalent and quadrivalent human papillomavirus (HPV) L1 (the major papillomavirus virion protein) virus-like particle (VLP) vaccines are regarded as safe, effective, and well established prophylactic vaccines. However, they have some inherent limitations, including a fairly high production and delivery cost, virus-type restricted protection, and no reported therapeutic activity, which might be addressed with the development of alternative dosing schedules and vaccine products. A change from a three-dose to a two-dose protocol for the licensed HPV vaccines, especially in younger adolescents (aged 9–13 years), is underway in several countries and is likely to become the future norm. Preliminary evidence suggests that recipients of HPV vaccines might derive prophylactic benefits from one dose of the bivalent vaccine. Substantial interest exists in both the academic and industrial sectors in the development of second-generation L1 VLP vaccines in terms of cost reduction—eg, by production in Escherichia coli or alternative types of yeast. However, Merck's nonavalent vaccine, produced via the Saccharomyces cerevisiae production system that is also used for their quadrivalent vaccine, is the first second-generation HPV VLP vaccine to be available on the market. By contrast, other pharmaceutical companies are developing microbial vectors that deliver L1 genes. These two approaches would add an HPV component to existing live attenuated vaccines for measles and typhoid fever. Prophylactic vaccines that are based on induction of broadly cross-neutralising antibodies to L2, the minor HPV capsid protein, are also being developed both as simple monomeric fusion proteins and as virus-like display vaccines. The strong interest in developing the next generation of vaccines, particularly by manufacturers in middle-to-high income countries, increases the likelihood that vaccine production will become decentralised with the hope that effective HPV vaccines will be made increasingly available in low-resource settings where they are most needed.